2019
DOI: 10.1136/bmjopen-2019-029667
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and processes of care across weekend and weekday hospitalisation for acute myocardial infarction, heart failure or stroke: an observational study of the National Readmission Database

Abstract: ObjectivesVariation in hospital resource allocations across weekdays and weekends have led to studies of the ‘weekend effect’ for ST elevation myocardial infarction (STEMI), non-ST elevation myocardial infarction (NSTEMI), heart failure (HF) and stroke. However, few studies have explored the ‘weekend effect’ on unplanned readmission. We aimed to investigate 30-day unplanned readmissions and processes of care across weekend and weekday hospitalisations for STEMI, NSTEMI, HF and stroke.DesignWe grouped hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“… 20 24 Similarly, other studies have shown that 30-day readmission rates are greater for NSTEMI compared to STEMI patients. 25 , 26 While our results were concordant with these studies, our study is one of the first to limit the analysis to the first 7 days (rather than first 30 days). These three characteristics likely represent a combination of recurrent and difficult-to-control conditions (e.g., rate control in atrial fibrillation) and patients with more complex underlying disease or comorbidities (NSTEMI and ICU admission).…”
Section: Discussionsupporting
confidence: 90%
“… 20 24 Similarly, other studies have shown that 30-day readmission rates are greater for NSTEMI compared to STEMI patients. 25 , 26 While our results were concordant with these studies, our study is one of the first to limit the analysis to the first 7 days (rather than first 30 days). These three characteristics likely represent a combination of recurrent and difficult-to-control conditions (e.g., rate control in atrial fibrillation) and patients with more complex underlying disease or comorbidities (NSTEMI and ICU admission).…”
Section: Discussionsupporting
confidence: 90%
“…Of those who survive to discharge, one in four patients will be readmitted and one in eight will die within a month of admission. 9 , 31 Quadruple therapy can reduce the risk of cardiovascular death or HF hospitalization by 62% compared with treatment with ACE‐I or ARB plus beta‐blocker alone, 1 and the time to onset of benefit of several HF medications is known to be <1 month. 2 , 3 , 4 As a result, guidelines recommend that patients are seen within 2 weeks of discharge by an HF specialist, 6 but fewer than half of care providers can meet this target.…”
Section: Discussionmentioning
confidence: 99%